2000
DOI: 10.1111/j.1745-9125.2000.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Self‐control Affect Survey Response? Applying Exploratory, Confirmatory, and Item Response Theory Analysis to Grasmick Et Al.'s Self‐control Scale*

Abstract: A General Theory of Crime has sparked a great deal of theoretical debate and empirical investigation. Tests of the theory have focused on measuring the core element, the latent trait of self-control. The majority of this research has used the 24-item scale developed by Grasmick et al. (1993), and a great deal of attention has been directed at the validity of this scale. Empirical debate revolves around the unidimensionality of the scale as established using conventional factor analytic techniques [exploratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
3
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 200 publications
(163 citation statements)
references
References 58 publications
4
155
3
1
Order By: Relevance
“…However, like previous researchers (e.g., Piquero et al, 2000), we found that the six-factor model was the most accurate model. Following modification indices, we used the following procedures to refine the six-factor model.…”
Section: Model Buildingcontrasting
confidence: 44%
See 2 more Smart Citations
“…However, like previous researchers (e.g., Piquero et al, 2000), we found that the six-factor model was the most accurate model. Following modification indices, we used the following procedures to refine the six-factor model.…”
Section: Model Buildingcontrasting
confidence: 44%
“…Exploratory factor analysis determines the number of factors that account for the covariation between the 24 items in the scale. Prior research Grasmick et al, 1993;Piquero et al, 2000;Vazsonyi et al, 2001) suggested that six factors will emerge with an eigenvalue greater than 1. These factors represent the six theorized dimensions of self-control.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not an issue for our models, which estimate single population models, and, accordingly, leave intercepts unconstrained. For applications of IRT to self-reported delinquency, see Osgood et al (2002) and Piquero et al (2000). 2 Much earlier, Maccoby, Johnson, and Church (1958:39) hypothesized that in disorganized neighborhoods, "individual adults will feel less responsible for guiding other people's children,"…”
Section: Endnotesmentioning
confidence: 99%
“…Recent attention to measurement in the social sciences covers a range of substantive and theoretical topics, including behavioral expectations (e.g., Manski 2004), social capital (e.g., Paxton 2002), democracy (Coppedge and Gerring, et al 2011), employment careers (Manzoni et al (2010), time use data from diaries (Kan and Pudney 2008), and family activities (Broege et al 2007). In criminology, the measurement of delinquent behavior (e.g., Osgood et al 2002;Piquero et al 2002) and self-control (e.g., Piquero et al 2000) has been examined using models for survey response. While measurement has been discussed in detail for individual-level psychometric models of test scores and survey responses, it is no less an issue for models of macro-ecological units, such as neighborhoods, communities, and schools.…”
mentioning
confidence: 99%